Oncofertility Knowledge and Communication: Comparison Between Medical and Surgical Oncologists and Breast Cancer Patients in Academic Chinese Centers - Biskup, Ewelina; Xin, Zhaochen; Li, Rui; Zucal, John P.; Lu, Yao; Sun, Yun; Appiah, Leslie Coker; Lindheim, Steven R.; Zhang, Hongwei (Frontiers in Surgery, 2021)
Background: As cancer has become a major public health issue in China, fertility preservation remains limited despite the wide application of Assisted Reproductive Technology (ART) throughout the country. Objective: This study aimed to identify gaps in knowledge and communication as well as referrals in the previous year regarding oncofertility among medical and surgical oncologists and breast cancer patients (BCPs) in Chinese academic settings to target areas of needed improvement. Materials and Methods: A WeChat online questionnaire was designed, distributed, and compared between medical and surgical oncology specialists and reproductive age BCPs in academic teaching settings in Shanghai. Results: Sixty-one medical and surgical oncologists and 125 BCPs responded to the survey. 63.3% of oncologists were familiar with the term “oncofertility” compared to 25.6% of BCPs (p<0.001). Oncologists were more likely to correctly know the costs associated with treatment (59.0% vs 32.0%, p<0.001); patient did not have to be married to undergo oncofertility treatment (50.8% vs 24.8%, p<0.001). Both oncologists and BCPs were similarly unlikely to know when patients could utilize cryopreserved tissue in the future (37.7% vs 22.2%, p=0.056). While oncologists reported they discussed all oncofertility options (41.0%) and offered psychological counseling (98.4%), significantly fewer BCPs reported receiving information on all options and offered counseling (3.2%, p<0.001 and 85.6%, p<0.01). Knowledge of oncofertility was the most important predictor for providing and receiving counseling from oncologists (OR 6.44 (95% CI 1.59-26.1, p=0.009) and BCPs (OR 3.73 95% CI 1.36-10.2, p=0.011. Overall, 57.4% of oncologists referred less than 10 patients and none referred more than 25 patients in the past year. Conclusion: Data suggests a significant knowledge gap and ineffective communication/comprehension exists between academic Chinese oncologists and BCPs. Continued education and raised awareness are needed to optimize utilization of oncofertility services in China.